2011
DOI: 10.1590/s0102-86502011000600018
|View full text |Cite
|
Sign up to set email alerts
|

Can Wistar rats be used as the normotensive controls for nerve morphometry investigations in spontaneously hypertensive rats (SHR)?

Abstract: PURPOSE:We compared the sural nerve morphology among Wistar (WR), Wistar-Kyoto (WKY) and Spontaneously hypertensive (SHR) rats, including the nerve fascicles and myelinated fibers morphometry. METHODS: Age matched (20 weeks) female WR (N=6), WKY (N=6) and SHR (N=7) had their right and left sural nerves removed, embedded in epoxy resin, and observed by light microscopy. Morphometric analysis was performed with the aid of computer software. RESULTS: Despite presenting the same age, WR were heavier than WKY and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…All sural nerves included in this study showed good preservation of structures and general morphological characteristics of the sural nerve fascicles of WR, WR + STZ, SHR and SHR + STZ were similar to those previously described [ 2 , 7 , 17 , 18 ]. The comparisons between segments for all groups showed no endoneural morphological differences on the same side.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…All sural nerves included in this study showed good preservation of structures and general morphological characteristics of the sural nerve fascicles of WR, WR + STZ, SHR and SHR + STZ were similar to those previously described [ 2 , 7 , 17 , 18 ]. The comparisons between segments for all groups showed no endoneural morphological differences on the same side.…”
Section: Resultssupporting
confidence: 82%
“…Both right and left sural nerves, from their origin in the hip (5–7 mm distal to the greater trochanter) through their distal branching at the lateral malleolus level, were carefully dissected without stretching, removed in one piece and placed in the fixative solution for an additional 12 hour. They were washed in cacodylate buffer, pH 7.2, and proximal (close to the origin) and distal (close to terminal branching) segments (of approximately 3 mm each) were cut and processed for epoxy resin embedding (EMbed-812®, Electron Microscopy Sciences, Hatfield, PA, USA) as described previously [ 2 , 7 , 17 , 18 ]. Samples of all four experimental groups were histologically processed at once so that they were submitted to absolutely the same experimental conditions throughout the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations